Does Helicobacter pylori play a role in the pathogenesis of childhood chronic idiopathic thrombocytopenic purpura? - Maryam Maghbool; Masood Maghbool; Mehdi Shahriari; Mehran Karimi (MDPI AG, 2009)
Idiopathic thrombocytopenic purpura (ITP) is an acute self-limited bleeding disorder that can progress to chronic form in 10-15% of the cases. Helicobacter pylori (H. pylori) infection is a possible cause of chronic ITP. We studied 30 children with resistant chronic ITP for H. pylori infection based on the detection of H. pylori fecal antigen. This retrospective study was based on data obtained from medical records of 30 children aged between five and 17 years (median age at ITP diagnosis was ten years). A specially-designed data sheet was used to record information on age, sex, duration of disease, family history of bleeding disorders, previous treatments and median platelet count. In patients with H. pylori infection, antimicrobial treatment consisted of amoxicillin, metronidazol and omeprazol. Response was assessed every month for one year and defined as complete (platelet count >150x109/L) or partial (platelet count between 50 and 150x109/L). We detected H. pylori infection in 5 patients. In 4 of them increased platelet count was seen during one year of follow-up and in one patient the platelet count was acceptable during six months. Although the pathological mechanism of H. pylori-induced thrombocytopenia was unclear in our patient sample, the assessment of H. pylori infection and use of eradication therapy should be attempted in chronic and resistant ITP patients.